Evaluation of hematologic parameters in children with Down syndrome - Hasibe Artaç; Hülya Özdemir (Genel Tıp Dergisi)
Objective: Congenital hematological disorders are frequently observed in Down syndrome (DS). In this study, we aimed to investigate peripheral blood-derived inflammation biomarkers such as neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, and eosinophil/monocyte ratio in patients with Down syndrome. Material and Methods: Ninety-eight patients with karyotypically ascertained DS and 103 healthy controls were included. All subjects were divided into three age groups: 0-2 years (34 patients, 34 controls), 2-6 years (32 patients, 33 controls), and >6 years (32 patients, 36 controls). Demographic, clinical, and laboratory data between June 2010 and December 2021 were written from the file records from the pediatric allergy and immunology department. Results: Lymphocyte, eosinophil, and EMR were found to be significantly lower in children with DS compared to controls in group 2 (2-6 years) and group 3 (>6 years). PLR was found to be higher in children with DS in group 2 and group 3. There was no statistically significant difference between DS and controls in group 1 (6 years), there was a statistically significant difference between DS and controls in terms of lymphocyte, eosinophil, PLR, and EMR variables (P>0.05). Conclusion: We found significant differences among lymphocyte, eosinophil, PLR, and EMR in patients with DS. As a result, these parameters should be evaluated carefully for clinical outcomes.